2011
DOI: 10.3342/ceo.2011.4.3.131
|View full text |Cite
|
Sign up to set email alerts
|

The Internet as a Source of Information for Patients Prior to Rhinoplasty

Abstract: ObjectivesTo determine the prevalence of Internet use by patients considering rhinoplasty and to identify the impact of such information on their decisions.MethodsProspective analysis of the impact of information received via the Internet by patients considering rhinoplasty on their decision-making prior to surgery. Eighty six patients, scheduled for post-traumatic or aesthetic rhinoplasty, received a questionnaire, consisting of 19 questions, which sought to evaluate their perception of the importance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…This is in contrast to other studies, which have reported significantly lower importance of the Internet; in one study, the Internet was the informal source of information in 23% of parents of children with ophthalmic diseases 6 and for 36.2% −58.1% in plastic surgery patients. 7,8 The relative importance of the Internet for the patients in our study could partially be explained by the relatively young patient age in our study (32.8 ± 8.6 years) as well as to the high Internet penetration in Poland.…”
Section: Discussionmentioning
confidence: 75%
“…This is in contrast to other studies, which have reported significantly lower importance of the Internet; in one study, the Internet was the informal source of information in 23% of parents of children with ophthalmic diseases 6 and for 36.2% −58.1% in plastic surgery patients. 7,8 The relative importance of the Internet for the patients in our study could partially be explained by the relatively young patient age in our study (32.8 ± 8.6 years) as well as to the high Internet penetration in Poland.…”
Section: Discussionmentioning
confidence: 75%
“…Even people with heavy strain due to their appearance, have nevertheless a fear of the possible complications. Nowadays, before such an operation, most people made an internet research 16 and read medical texts about such risks. A survey on behalf of the Federal Institute for food and agriculture 17 found that every fifth cosmetic operation in Germany is associated with complications (22% women, 8% men).…”
Section: Discussionmentioning
confidence: 99%
“…Useful information for model selection can be obtained from using AIC and BIC together, particularly from trying as far as possible to find models favoured by both criteria. Quantitatively, the BIC puts more penalty on the log-likelihood function and the BIC favours more parsimonious models [ 28 ]. In the present study the neighbourhood-based Poisson regression was favoured by AIC, BIC and adjusted pseudo R 2 indices, although the distance-based Poisson model was closer to the neighbourhood-based GLMM results than was the nonspatial Poisson regression.…”
Section: Discussionmentioning
confidence: 99%